Integrating product emotions study in the industrial design education for sustaining affective consumers - Raja Ahmad Effendi, Raja Ahmad Azmeer; Mohd. Salleh, Suleiman; Ibrahim, Rahinah (Faculty of Design & Architecture, Universiti Putra Malaysia, 2006)
This article highlights the importance of product emotions study in the industrial design education. The incorporation of product emotions during the design of an artefact is important as it embodies the socio-cultural preference towards that artefact, hence supporting one of the three sustainable development components—social sustainability. Therefore, through the application of product emotions study, Malaysian products could elicit positive emotions that will lead to consumer-product’s ‘affective sustainability.’ We conducted a preliminary survey among the industrial design academia to gauge how we can effectively incorporate the product emotions component into the Malaysian tertiary curriculum. We first present a selected background literature on product emotions and explain the types of response processing using examples from the market. We then explain our research method and present the results and analysis. At the conclusion of this article, we recommend how industrial design education can integrate the aspect of product emotions in its curriculum and highlight the need for research in this area if Malaysian products wish to gain sustainable affection in the global markets. We hope that the successful integration of product emotions will enable local manufacturers to improve their sales revenue and develop larger market for their products.